2012
DOI: 10.1002/path.4076
|View full text |Cite
|
Sign up to set email alerts
|

Notch‐3 receptor activation drives inflammation and fibrosis following tubulointerstitial kidney injury

Abstract: Kidney diseases impart a vast burden on affected individuals and the overall health care system. Progressive loss of renal parenchymal cells and functional decline following injury are often observed. Notch-1 and -2 receptors are crucially involved in nephron development and contribute to inflammatory kidney diseases. We specifically determined the participation of receptor Notch-3 following tubulointerstitial injury and in inflammatory responses. Here we show by heat map analyses that Notch-3 transcripts are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 36 publications
5
112
1
Order By: Relevance
“…25 We recently showed that Notch3-HeyL pathway activation promotes tubulointerstitial fibrosis and inflammation by increasing MCP-1 synthesis in the UUO model. 11 These findings suggest that activation of the Notch3-HeyL pathway can be a common renal pathogenic mechanism promoting glomerulosclerosis, tubulointerstitial fibrosis, and renal inflammation. It was also recently shown that the inhibition of HeyL induces the decrease of proinflammatory cytokines in breast cancer cells.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…25 We recently showed that Notch3-HeyL pathway activation promotes tubulointerstitial fibrosis and inflammation by increasing MCP-1 synthesis in the UUO model. 11 These findings suggest that activation of the Notch3-HeyL pathway can be a common renal pathogenic mechanism promoting glomerulosclerosis, tubulointerstitial fibrosis, and renal inflammation. It was also recently shown that the inhibition of HeyL induces the decrease of proinflammatory cytokines in breast cancer cells.…”
Section: Discussionmentioning
confidence: 88%
“…A similar interaction between inflammation and Notch3 neoexpression was also observed in renal tubular epithelial cells in our previous study using the unilateral ureteral obstruction (UUO) model, a classic model of tubular inflammation. 11 Recent studies observed an interaction between Notch3 and p65/NF-kB to regulate T cell function under control conditions or in disease. 23,24 A pathogenic role for the Notch3 receptor was first described in CADASIL syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40,41 Physical contact between cells induces the Notch signaling pathway. In liver sinusoids, KCs, LSECs, HSCs, lymphocytes, and hepatocytes contact each other and have a capacity to induce DLL4 expression in some disease setting.…”
Section: Dll4 and Chemokine In Liver Damagementioning
confidence: 99%